2016
DOI: 10.3389/fphar.2016.00247
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive and System Review for the Pharmacological Mechanism of Action of Rhein, an Active Anthraquinone Ingredient

Abstract: Rhein is a major medicinal ingredient isolated from several traditional Chinese medicines, including Rheum palmatum L., Aloe barbadensis Miller, Cassia angustifolia Vahl., and Polygonum multiflorum Thunb. Rhein has various pharmacological activities, such as anti-inflammatory, antitumor, antioxidant, antifibrosis, hepatoprotective, and nephroprotective activities. Although more than 100 articles in PubMed are involved in the pharmacological mechanism of action of rhein, only a few focus on the relationship of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 145 publications
2
77
0
4
Order By: Relevance
“…It possesses two hydroxide residues, one carboxyl, and has very strong chemical polarity (Malterud et al, 1993). Although Rhein has antioxidant, antiviral, antiinflammatory, antitumor, anti-fibrosis, hepatoprotective, and nephroprotective activities (Sun et al, 2016;Bi et al, 2018), the anti-RSV pneumonia of Rhein has not yet been clearly defined. Furthermore, previous literature studies found that Rhein had the anti-inflammatory effect through intervention NLRP3 signal in RAW264.7 macrophages, and zebrafish .…”
Section: Introductionmentioning
confidence: 99%
“…It possesses two hydroxide residues, one carboxyl, and has very strong chemical polarity (Malterud et al, 1993). Although Rhein has antioxidant, antiviral, antiinflammatory, antitumor, anti-fibrosis, hepatoprotective, and nephroprotective activities (Sun et al, 2016;Bi et al, 2018), the anti-RSV pneumonia of Rhein has not yet been clearly defined. Furthermore, previous literature studies found that Rhein had the anti-inflammatory effect through intervention NLRP3 signal in RAW264.7 macrophages, and zebrafish .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is reasonable to propose a hypothesis that rhein derived from rhubarb is responsible for most of the observed neuroprotection following TBI. Rhein has extensive pharmacological effects, including anti-inflammatory, antitumor, antifibrosis, hepatoprotective, nephroprotective, antimicrobial and anti-oxidant activities171819. Unfortunately, the molecular mechanism underlying the protective effects on TBI remains unknown.…”
mentioning
confidence: 99%
“…Another natural compound, the anthranoid 4,5-dihydroxyanthraquinone-2-carboxylic acid (rhein) exhibits anti-inflammatory, antioxidant, antifibrosis, neuroprotective and antitumor activities [82,83]. The antitumor activity is attributed to the inhibition of MAPK, PI3K-AKT and HIF-1 signaling pathways and the down-regulation of VEGF signaling pathway [83,84]. Blacher and colleagues [85], aiming at demonstrating that the inhibition of the ectoenzyme CD38 in tumor microenvironment can attenuate glioma progression, conducted a study using a syngeneic mouse glioma progression model.…”
Section: Drugs For Gbm Treatment Administered Intranasallymentioning
confidence: 99%